Bambusicola autumnalis sp. nov., a bambusicolous ascomycete from Sichuan province, China - Liang, Rui-Ru; Zhang, Sheng-Nan; Liu, Jian-Kui (Phytotaxa, 2023)
During the survey of microfungi diversity in Sichuan province, China, a new bamboo inhabiting ascomycete Bambusicola autumnalis was identified and introduced in this study. Bambusicola autumnalis is characterized by having immersed to erumpent ascostromata, and fusiform, hyaline, 1-septate ascospores surrounded by an inconspicuous mucilaginous sheath, which fits well with the sexual morph of Bambusicola. The phylogenetic analysis based on multi-gene (SSU, ITS, LSU, RPB2, TEF1-α) dataset of taxa within the family Bambusicolaceae showed that B. autumnalis formed a sister lineage to B. guttulata within Bambusicola and representing as a distinct species. Morpho-phylogenetic evidence revealed B. autumnalis is distinct from other Bambusicola species. Notes on the phylogenetic placement and identification of the new species are provided.